INFLUENCE OF LABOR SERVICE FACILITY ON INFANT MORTALITY RATE IN INDONESIA - Vivi Ratna Ayuningrum; Vilda Eka Febrianti; Anik Nur Khasanah; Fahmi Arif Kurnianto; Fahrudi Ahwan Ikhsan (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2019)
Indonesia is a country that has high infant mortality rate among other ASEAN countries, Infant mortality rate is also the first indicator in determining child health status in Indonesia. Indonesia still has a fairly high infant and under-five mortality rate. Baby mortality problems in Indonesia have problems with transmission, especially malaria, diarrhea that causes nutritional problems that can result in child mortality. The infant mortality rate is the number of infant deaths (before the age of one year) that occurs at birth per 1000 babies. Is a method of measurement that is used specifically to determine the infant mortality rate. IMR is usually used as an indicator in the measurement of the welfare of the population. Data collection technique using sekounder data sourced from BPS 2013 and DG of Disease Prevention and Control, Ministry of Health of Indonesia 2017. Data analysis technique used is product moment correlation to know strength of relation between 2 variables. Based on the existing percentage in the data ratio of doctors in 33 provinces in Indonesia obtained the results of 16.02. there are 21 provinces that have the ratio of doctors who have met the minimum requirements. So it can be concluded that there are still many provinces that have less doctors. Provinces with the lowest IMR data were found in Yogyakarta Province with IMR rates of 12. The ratio of doctors in DI Yogyakarta had sufficient numbers so the infant mortality rate in the area was low. The availability of adequate doctors in Indonesia minimizes infant and maternal mortality. Number of doctors in Indonesia. The results showed that the knowledge of postpartum mother about the danger of newborn respondent with good knowledge level. Keyword : child health status, nutritional problems, mortality rate References IFA, Hoday et al. ANALISIS SOSIAL EKONOMI TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT TENGGER GUNUNG BROMO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 169-175, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12305>. Date accessed: 12 aug. 2019. PAHLEVY, Fahrizal Novan; APRIYANTO, Bejo; ASTUTIK, Sri. KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT DAERAH WISATA BROMO SEBAGAI PENGEMBANGAN KESEJAHTERAAN HIDUP. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 172-189, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12177>. Date accessed: 12 aug. 2019. HARYANTI, Titik Umaiyah. PERANAN PANTAI DALAM KONDISI SOSIAL EKONOMI MASYARAKAT DISEKITAR PANTAI BENTAR KABUPATEN PROBOLINGGO JAWA TIMUR.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 1, n. 1, p. 12-16, aug. 2018. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/8336>. Date accessed: 12 aug. 2019. UMAM, Muhammad Fikri; ALHIDAYAH, Yazid; FAUZIYAH, Rita. ANALISIS MATERIAL ENDAPAN VULKAN GUNUNG SEMERU KABUPATEN LUMAJANG. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 92-98, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11522>. Date accessed: 12 aug. 2019. SETYAWAN, Muhammad Alif; APRIYANTO, Bejo; ASTUTIK, Sri. ANALISIS KARAKTERISTIK ENDAPAN MARINE DAN PENGARUHNYA BAGI SEKTOR PERTANIAN DAN PERAIRAN DI PESISIR SELATAN PANTAI PANCER KECAMATAN PUGER KABUPATEN JEMBER JAWA TIMUR. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 141-154, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11760>. Date accessed: 12 aug. 2019. KURNIANTO, Fahmi Arif et al. THE ENVIRONMENT ANALYSIS OF POPULATION GROWTH, UNEMPLOYMENT, AND POVERTY LEVEL IN MAESAN DISTRICT BONDOWOSO REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 113-121, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8439>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i2.8439. SARI, Eva Kurnia; PRAMESTY, Dinda Ayu. THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 3, p. 50-58, jan. 2019. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/9300>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i3.9300. LESTARI, Dwi et al. ANALISIS FENOMENA GEOGRAFI FISIK PADA PENGUKURAN PROSES DAN HASIL PROSES BENTANG ALAM JAWA TENGAH. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 110-118, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11626>. Date accessed: 12 aug. 2019. ZAHROH, Faidatuz; ELFIANI, Vira; H, Arya Bagas. ASPEK SOSIAL DAERAH KARST PUGER DALAM PRESPEKTIF EKONOMI. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 155-160, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11780>. Date accessed: 12 aug. 2019. NURIYANTO, Muhammad Zaid; FIRMANSYAH, Fahrul Agil; PRASETYONO, Ica. ANALISIS PERUBAHAN BENTANG GEOMORFOLOGI PANTAI BENTAR KABUPATEN PROBOLINGGO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 99-109, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11523>. Date accessed: 12 aug. 2019.